Evaluating the Bioactivity of a Novel Antimicrobial and Anticancer Peptide, Dermaseptin-PS4(Der-PS4), from the Skin Secretion of Phyllomedusa sauvagii - Dong Chen; Xiaowei Zhou; Xi Chen; Linyuan Huang; Xinping Xi; Chengbang Ma; Mei Zhou; Lei Wang; Tianbao Chen (Molecules, 2019)
Dermaseptins belonging to a large family of cationic membrane-disruption antimicrobial peptides display extensive antibacterial and antiproliferative activities depending on a coil-to-helix transition and the specific structural parameters. Herein, a novel dermaseptin peptide named Der-PS4 was discovered from the skin secretion of the waxy monkey tree frog, Phyllomedusa sauvagii. The complementary DNA (cDNA)-encoding precursor was obtained relying on “shotgun” cloning, and afterwards, a mature peptide amino acid sequence was identified by reverse-phase high performance liquid chromatography (RP-HPLC) and MS/MS. Specimens were chemically synthesized and applied for further functional studies. Structural analysis demonstrated a higher α-helical content in the membrane-mimetic environment compared with that in the ammonium acetate/water circumstance. Der-PS4 displayed a broad spectrum of antimicrobial activities against tested pathogenic microorganisms, however, exhibiting slight membrane-damaging effectiveness towards horse red blood cells. Coincident with the inhibitory activities on pathogens, Der-PS4 also showed considerable biofilm eradicating impact. Also, Der-PS4 penetrated cell membrane in a relative short period under each minimum bactericidal concentration. In addition, Der-PS4 possessed antiproliferative capacity against five cancer cell lines, while presenting slight suppressing effect on human microvascular endothelial, HMEC-1. These findings provide a promising insight for the discovery and development of novel drugs from a natural source.